2021
DOI: 10.46498/reduipb.v25i1.1425
|View full text |Cite
|
Sign up to set email alerts
|

Análisis empírico sobre el rendimiento académico de los estudiantes en la asignatura de inglés con el uso de Voscreen

Abstract: La tecnología es parte importante de la sociedad actual y una interesante herramienta para mejorar el aprendizaje, su uso responde a la naturaleza lúdica que la caracteriza. El objetivo de la presente investigación es conocer si existe una correlación entre el uso frecuente de la aplicación VoScreen y el rendimiento académico de los estudiantes de idioma inglés de la Universidad Estatal de Bolívar, Ecuador. Esta investigación cuantitativa experimental, se basa en un muestreo no probabilístico intencional, apli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Some related studies show how games use themselves is not a solution for increasing motivation. Cultural and situational factors play a role in games' effectiveness [32] along with voluntary participation, which significantly increases motivation although the use of games is appreciated even if participation is not voluntary [33] although other studies mention a correlation with improved academic performance even when participation is not voluntary [34]. Anyway, the inclusion of games would have a positive effect on intrinsic need satisfaction [35].…”
Section: Gamification and Motivationmentioning
confidence: 99%
“…Some related studies show how games use themselves is not a solution for increasing motivation. Cultural and situational factors play a role in games' effectiveness [32] along with voluntary participation, which significantly increases motivation although the use of games is appreciated even if participation is not voluntary [33] although other studies mention a correlation with improved academic performance even when participation is not voluntary [34]. Anyway, the inclusion of games would have a positive effect on intrinsic need satisfaction [35].…”
Section: Gamification and Motivationmentioning
confidence: 99%
“…When the related literature is examined, it is seen that several studies have investigated the impact of Voscreen on various aspects, including vocabulary improvement, listening, and self-regulated learning. Carrión et al (2021) explored the potential correlation between the regular use of VoScreen and the academic performance of English language students at the tertiary level. The findings revealed that students had higher performance at the end of the intervention.…”
Section: Voscreen As An Educational Toolmentioning
confidence: 99%